A taxonomic revision of the genus Xylota Meigen (Diptera: Syrphidae) in Korea - Jeong, Soo-Hyun; Han, Ho-Yeon (Zootaxa, 2019)
As a result of the study of the hoverfly subtribe Xylotina in Korea, we have recognized the following 14 Xylota species, including eight new to the Korean syrphid fauna (marked with asteristks) and three new to science: X. abiens, X. amaculata*, X. atricoloris*, X. coquilletti, X. filipjevi*, X. fo*, X. ignava, X. pseudoignava*, X. spurivulgaris*, X. tarda*, X. umbrosa*, X. hauseri sp. n., X. orientiflorum sp. n., and X. xanthotarsis sp. n. Among these species, we clarified the identities of three previously confused species, X. coquilletti, X. spurivulgaris and X. fo, which had been collectively identified as a single species, X. coquilletti, in the Korean literature. In addtion, we provided unequivocal characters to separate two sibling species pairs based on their external characters including genitalic structure (X. hauseri sp. n. vs. X. umbrosa; X. pseudoignava vs. X. xanthotarsis sp. n.; X. filipjevi vs. X. tarda). In order to aid accurate identification of the Korean Xylota, diagnoses, descriptions, and color photographs of external structures including male genitalia are provided. For the taxonomic key, we included all the Korean genera of the subtribe Xylotina (Xylota, Brachypalpus and Chalcosyrphus).